Preparation of MoNiCoFe multi-metal self-supporting electrocatalyst
By preparing MoNiCoFe multi-metal self-supporting electrocatalysts and utilizing the electronic synergistic effect and interface coupling between multiple metals, the charge transfer dynamics are optimized, the high price and performance bottleneck problems of existing electrocatalysts are solved, and efficient and stable hydrogen production performance by water electrolysis is achieved.
Patent Information
- Application Number
- CN202510970651.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-15
- Publication Date
- 2025-10-03
AI Technical Summary
Existing electrocatalysts such as Pt catalysts have problems of high prices and limited reserves in hydrogen production by water electrolysis. At the same time, single metal catalysts face the problems of limited active sites, insufficient conductivity and excessively high energy barriers for intermediate adsorption.
MoNiCoFe multi-metal self-supporting electrocatalyst is used to construct a hierarchical porous micron column structure through a hydrothermal method. Foam iron is combined as a conductive substrate. The electronic synergistic effect and interface coupling between multi-metals are utilized to optimize the charge transfer dynamics and reduce the reaction energy barrier.
The electrocatalytic performance is significantly improved, showing activity similar to that of Pt catalysts, and has excellent stability and low overpotential under alkaline conditions. It can work continuously at high current density and provides a large active specific surface area and structural stability.
Smart Images

Figure HDA0005499804070000011 
Figure HDA0005499804070000012 
Figure HDA0005499804070000013
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalytic hydrogenation, and in particular to the preparation of a MoNiCoFe multi-metal self-supporting electrocatalyst. Background Art
[0002] As a green and renewable energy source, hydrogen has become a key research topic in the global energy transition. Hydrogen production through water electrolysis is considered one of the most promising hydrogen production methods due to its efficient H2 production (reaching 99.6%). Therefore, the development of electrocatalysts with high efficiency, long-term stability, and low cost has become a core issue in current electrocatalytic research. In the electrocatalytic hydrogen evolution reaction, Pt and its derivatives are considered ideal electrocatalytic materials due to their excellent catalytic activity. However, the high price and limited reserves of Pt significantly limit its feasibility in large-scale applications. Therefore, improving the efficiency of Pt or identifying alternative materials with similar performance have become key research directions to address this issue. Transition metal catalysts have attracted considerable attention in the field of electrocatalysis due to their tunable d-orbital electronic structure and rich redox activity. However, single-metal catalysts often face challenges such as limited active sites, insufficient conductivity, and high intermediate adsorption barriers. In contrast, multimetallic composite catalysts, through electronic synergy and interfacial coupling between different metals, can significantly optimize charge transfer kinetics and reduce reaction energy barriers, becoming an effective strategy to overcome performance bottlenecks. Summary of the Invention
[0003] Based on the above background, the present invention provides a simple and low-cost method to prepare a MoNiCoFe multi-metal self-supporting electrocatalyst as an electrocatalytic hydrogen evolution catalyst material with the advantages of high electrocatalytic performance and good stability.
[0004] The object of the present invention is achieved like this:
[0005] A preparation method of a MoNiCoFe multi-metal self-supporting electrocatalyst comprises the following steps:
[0006] (1) Slowly add 200 mL of 0.038 mM NiSO4·5H2O solution to 300 mL of 0.1 mM (NH)6Mo7O at 80°C. 24 ·4H2O solution, evaporate half of it, filter the solution while hot, and cool the filtrate to room temperature to obtain blue-green crystals (NH4)4[NiMo6O 24 H6]·7H2O(NiMo6).
[0007] (2) Immerse the foamed iron in 1M hydrochloric acid, acetone, anhydrous ethanol and deionized water respectively and ultrasonicate for 30 minutes, then dry in an oven for later use. 24 H6]·6H2O polyacid (0.10 g, 0.070 mmol) and Co(NO)3 (0.043 g, 0.18 mmol) were dissolved in 10 mL of deionized water and placed on a 1*1.5 cm 2 Foam iron (abbreviated as IF) was stirred at room temperature for 30 min.
[0008] (3) The stirred foamed iron was placed in a 160°C forced air drying oven for 24 hours, cooled, washed and dried. The product Mo4O 11 / NiCoFe-LDH@IF (NiCoFe-LDH is a layered NiCoFe trimetallic hydroxide, LDH is the abbreviation for Layered Double Hydroxides).
[0009] The above-mentioned MoNiCoFe multi-metal self-supporting electrocatalyst is mainly used in the electrocatalytic decomposition of water to produce hydrogen.
[0010] The above application method is as follows: select (NH4)4[NiMo6O 24 A self-supporting catalyst Mo4O with a hierarchical porous micron column structure was constructed by a hydrothermal method using H6]·6H2O as a precursor, cobalt nitrate as an auxiliary cobalt source, and iron foam as a conductive substrate. 11 / NiCoFe-LDH@IF exhibits excellent electrocatalytic activity and stability in alkaline electrolyte.
[0011] Compared with the prior art, the present invention has the following characteristics:
[0012] The present invention selects (NH4)4[NiMo6O 24 A self-supporting catalyst Mo4O with a hierarchical porous micron column structure was constructed by a hydrothermal method using H6]·6H2O as a precursor, cobalt nitrate as an auxiliary cobalt source, and iron foam as a conductive substrate. 11 / NiCoFe-LDH@IF is a stable and catalytically active alkaline water electrolysis catalyst. The composition, morphology and electronic structure of the catalyst were systematically characterized, and it was found that its metal-oxide heterogeneous interface simultaneously increased the reaction rates of hydrogen evolution reaction and oxygen evolution reaction. Electrochemical tests confirmed that it has a high conductivity at 10 mA cm under alkaline conditions. -2 The overpotentials of hydrogen evolution reaction are 48mV and oxygen evolution reaction are 250mV respectively. There is no voltage decay of hydrogen evolution reaction after continuous operation for 48 hours and no voltage decay of oxygen evolution reaction after continuous operation for 24 hours. -2Even at high current densities, it can still exhibit low overpotentials, which are 353mV (hydrogen evolution reaction) and 549mV (oxygen evolution reaction), respectively. With the chemical composition advantages and inheritance of electronic structure characteristics of polyoxometalates, the active species in the multi-metal composite catalyst significantly optimize the charge transfer dynamics and reduce the reaction energy barrier through the electronic synergistic effect and interface coupling between multiple metals, thereby improving the catalytic performance. At the same time, the micron columnar structural units and the three-dimensional porous network structure can provide a large active specific surface area and structural stability, effectively promoting charge transfer and material diffusion, further enhancing the catalytic performance, and preparing a polyacid-derived heterometallic self-supported hydroxide catalyst material. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is the X-ray diffraction spectrum of a MoNiCoFe multi-metal self-supporting electrocatalyst material prepared in Example 1 of the present invention.
[0014] Figure 2 This is an X-ray photoelectron spectrum of a MoNiCoFe multi-metal self-supporting electrocatalyst material prepared in Example 1 of the present invention.
[0015] Figure 3 This is a scanning electron microscope image of a MoNiCoFe multi-metal self-supporting electrocatalyst material prepared in Example 1 of the present invention.
[0016] Figure 4 This is a transmission electron microscope image of a MoNiCoFe multi-metal self-supporting electrocatalyst material prepared in Example 1 of the present invention.
[0017] Figure 5 These are electrochemical test graphs of a MoNiCoFe multi-metal self-supporting electrocatalyst material prepared in Example 1 of the present invention at different reaction times.
[0018] Figure 6 These are electrochemical test diagrams of a MoNiCoFe multi-metal self-supporting electrocatalyst material prepared in Example 1 of the present invention at different reaction temperatures.
[0019] Figure 7 This is a linear scanning test diagram of a MoNiCoFe multi-metal self-supporting electrocatalyst material prepared in Example 1 of the present invention.
[0020] Figure 8 This is the Tafel slope diagram of a MoNiCoFe multi-metal self-supporting electrocatalyst material prepared in Example 1 of the present invention.
[0021] Figure 9 This is a current density-speed sweep diagram of a MoNiCoFe multi-metal self-supporting electrocatalyst material prepared in Example 1 of the present invention (the inset is a cyclic voltammetry curve diagram).
[0022] Figure 10 This is a test chart of the water electrolysis stability of a MoNiCoFe multi-metal self-supporting electrocatalyst material prepared in Example 1 of the present invention.
[0023] Figure 11 This is a flow chart of the experiment for preparing a MoNiCoFe multi-metal self-supporting electrocatalyst material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] The present invention will be described in detail below with reference to the accompanying drawings and embodiments.
[0025] Example 1, a MoNiCoFe multi-metal self-supporting electrocatalyst material, comprising the following preparation steps:
[0026] (1) Slowly add 200 mL of 0.038 mM NiSO4·5H2O solution to 300 mL of 0.1 mM (NH)6Mo7O at 80°C. 24 ·4H2O solution, evaporate half of it, filter the solution while hot, and cool the filtrate to room temperature to obtain blue-green crystals (NH4)4[NiMo6O 24 H6]·7H2O(NiMo6).
[0027] (2) Immerse the foamed iron in 1M hydrochloric acid, acetone, anhydrous ethanol and deionized water respectively and ultrasonicate for 30 minutes, then dry in an oven for later use. 24 H6]·6H2O polyacid (0.10 g, 0.070 mmol) and Co(NO)3 (0.043 g, 0.18 mmol) were dissolved in 10 mL of deionized water and a piece of foamed iron (1*1.5 cm 2 ), stirred at room temperature for 30 min. Weigh (NH4)4[NiMo6O 24 H6]·6H2O polyacid (0.10 g, 0.070 mmol) and Co(NO)3 (0.043 g, 0.18 mmol) were dissolved in 10 mL of deionized water and a piece of foamed iron (1*1.5 cm 2 ), and stirred at room temperature for 30 min.
[0028] (3) The stirred foamed iron was placed in a 160°C forced air drying oven for 24 hours, cooled, washed and dried. The product Mo4O 11 / NiCoFe-LDH@IF.
[0029] The present invention will be further described below with reference to the accompanying drawings and embodiments:
[0030] like Figure 1The figure shows an X-ray diffraction spectrum of a polyacid-derived heterometallic oxide material. The XRD system was used to analyze the Mo4O 11 The crystal phase composition of the / NiCoFe-LDH@IF composite material shows the coexistence of multiple crystal phases in the composite material. 11 / NiCoFe-LDH@IF composite materials contain five characteristic phases: orthorhombic phase Mo4O 11 The (211) and (440) crystal planes of (JCPDS No. 05-0337) correspond to the characteristic peaks of 22.2° and 70.8°; the (110) and (101) crystal planes of hexagonal NiOOH (JCPDS No. 27-0956) produce strong diffraction responses at 28.2° and 36.1°; the structure of monoclinic CoOOH (JCPDS No. 26-0480) is confirmed by the diffraction peaks of 27.9° (120) and 48.0° (131). The FeOOH (JCPDS No. 18-0639) phase shared by the two systems shows characteristic peaks at 18.1° (020) and 33.4° (400), while the metallic phase of Fe (JCPDS No. 06-0696) is verified by the peak groups at 44.7° (110), 65.0° (200), and 82.3° (211).
[0031] like Figure 2 The figure shows an X-ray photoelectron energy diagram of a MoNiCoFe multi-metal self-supporting electrocatalyst material. The XPS full spectrum scan and high-resolution spectrum peak fitting are used to analyze the Mo4O 11 Chemical state and coordination environment of metal elements in / NiCoFe-LDH@IF composite materials. Co 2p orbital presents 781.5eV (2p 3 / 2 ) and 797.8eV(2p 1 / 2 ) characteristic peak, and its satellite peaks are located at 785.2eV and 803.9eV, which is consistent with Co 2+ The electronic configuration of Mo 3d spectrum is shown at 231.7eV (Mo 5+ 3d 5 / 2 ) and 235.2eV(Mo 5+ 3d 3 / 2 )、232.9eV(Mo 6+ 3d 5 / 2 ) and 236.0eV(Mo 6+ 3d 3 / 2 ) Four-peak fitting, the surface molybdenum presents Mo 5+ / Mo 6+ Mixed valence state. Ni 2p orbital characteristic peaks are located at 856.5eV (2p 3 / 2 )、873.9eV(2p 1 / 2), the satellite peaks are located at 861.9eV (+5.4eV) and 879.3eV (+5.4eV), confirming that Ni 2+ Oxygen species distribution: the weak peak at 530.6eV is attributed to MO, and the strong peak at 531.8eV is attributed to OH - The weak peak at 533.0eV is attributed to the oxygen in the adsorbed water molecules. The XPS results further confirm that the component is Mo4O 11 / NiCoFe-LDH / Fe, confirmed that Mo4O 11 Successful assembly of / NiCoFe-LDH@IF.
[0032] like Figure 3 The figure shows a scanning electron microscope image of a polyacid-derived heterometallic self-supporting oxide catalyst material. The SEM test was used to measure the Mo4O 11 The morphology and microstructure of the Mo4O / NiCoFe-LDH@IF composite material were characterized. 11 The morphology of the NiCoFe-LDH@IF sample is shown in Figures a, b, and c. The sample exhibits a highly ordered rod-like structure, with uniform microrod size distribution, smooth surfaces, and regular arrangement along specific crystal directions. The microrods are approximately 5 microns long and less than 1 micron in diameter. This regular microrod array increases the catalyst's specific surface area, promoting rapid electron conduction along the axial direction, effectively improving the material's conductivity and, consequently, its performance in hydrogen and oxygen evolution reactions. The elemental distribution map, shown in Figures dh, confirms the uniform distribution of Co, Fe, Mo, Ni, and O along the microrods, with a distinct Fe gradient concentration field at the interface with the iron foam substrate.
[0033] like Figure 4 Transmission electron microscopy image of a MoNiCoFe multi-metal self-supporting electrocatalyst material, Mo4O 11 The low-resolution transmission electron microscopy image of the NiCoFe-LDH@IF composite material shows a relatively regular lamellar morphology with no obvious agglomeration. The high-resolution transmission electron microscopy image further shows multiple crystal plane stripes inside the material, and the spacing between different crystal planes is relatively stable, indicating that the sample has the characteristics of polycrystalline or multi-phase coexistence. The corresponding crystal plane spacings are 0.48nm, 0.21nm, 0.25nm and 0.45nm, respectively, corresponding to the (020) crystal plane of FeOOH (JCPDS No.18-0639), the (210) crystal plane of NiOOH (JCPDS No.27-0956), the (130) crystal plane of CoOOH (JCPDS No.26-0480) and the Mo4O 11 (401) crystal plane (JCPDS No.05-0337).
[0034] like Figure 5 This is an electrochemical test diagram of a MoNiCoFe multi-metal self-supporting electrocatalyst material under different reactions. The consistency verification of multi-dimensional electrochemical characterization data finally established that 24h is the best reaction time for Mo4O 11 Optimal synthesis time of / NiCoFe-LDH@IF composite materials.
[0035] like Figure 6 This is the electrochemical test diagram of a polyacid-derived heterometallic oxide material at different reaction temperatures. The consistency verification of multi-dimensional electrochemical characterization data finally established that 180℃ is the best temperature for Mo4O 11 The optimal synthesis temperature of / NiCoFe-LDH@IF composite material.
[0036] like Figure 7 This is a linear scan test diagram of a MoNiCoFe multi-metal self-supporting electrocatalyst material. 11 The NiCoFe-LDH@IF catalyst not only exhibits excellent catalytic activity comparable to that of the Pt / C catalyst in the hydrogen evolution reaction, but also maintains a low overpotential level in the high current density range of the oxygen evolution reaction.
[0037] like Figure 8 This is the Tafel slope diagram of a MoNiCoFe multi-metal self-supporting electrocatalyst material. The Tafel slope analysis results are highly consistent with the overpotential of the linear sweep voltammetry test, further verifying that Mo4O 11 / NiCoFe-LDH@IF composite material has excellent electrocatalytic performance.
[0038] like Figure 9 This is a current density-speed scan diagram of a MoNiCoFe multi-metal self-supporting electrocatalyst material (the inset is a cyclic voltammetry curve). The double layer capacitance was measured using the CV method. As shown in the figure, Mo4O 11 C / NiCoFe-LDH@IF electrode dl The value is 86mF cm -2 This result indicates that the catalyst has a larger electrochemically active surface area, which means that more active sites are exposed and can accommodate more reaction intermediates at the same time, thereby significantly improving the catalytic reaction rate.
[0039] like Figure 10 This is a test diagram of the stability of water electrolysis of a MoNiCoFe multi-metal self-supporting electrocatalyst material. 11 The X-ray diffraction and X-ray photoelectron spectroscopy characterization results of the NiCoFe-LDH@IF composite material before and after the electrochemical reaction and the cyclic stability test fully verified the long-range electrocatalytic stability of the catalyst.
[0040] Figure 11 This is a flow chart of the experiment for preparing a MoNiCoFe multi-metal self-supporting electrocatalyst material prepared in Example 1 of the present invention.
Claims
1. A method for preparing a MoNiCoFe multi-metal self-supporting electrocatalyst, the preparation method is as follows: (1) Slowly add 200 mL of 0.038 mM NiSO4·5H2O solution to 300 mL of 0.1 mM (NH)6Mo7O at 80°C. 24 ·4H2O solution, evaporate half of it, filter the solution while hot, and cool the filtrate to room temperature to obtain blue-green crystals (NH4)4[NiMo6O 24 H6]·7H2O(NiMo6). (2) Immerse the foamed iron in 1M hydrochloric acid, acetone, anhydrous ethanol and deionized water respectively and ultrasonicate for 30 minutes, then dry in an oven for later use. 24 H6]·6H2O polyacid (0.10 g, 0.070 mmol) and Co(NO)3 (0.043 g, 0.18 mmol) were dissolved in 10 mL of deionized water and placed on a 1*1.5 cm 2 Foam iron (IF), stir at room temperature for 30 minutes. (3) The stirred foamed iron was placed in a 160°C forced air drying oven for 24 hours, cooled, washed and dried. The product Mo4O 11 / NiCoFe-LDH@IF.
2. The application of a MoNiCoFe multi-metal self-supporting electrocatalyst as described in claim 1, characterized in that: The invention relates to the preparation of a MoNiCoFe multi-metal self-supporting electrocatalyst and its application in the field of electrocatalytic water decomposition and hydrogen production.
3. The use of a MoNiCoFe multi-metal self-supporting electrocatalyst according to claim 2, characterized in that: The application method is as follows: select (NH4)4[NiMo6O 24 A self-supporting catalyst Mo4O with a hierarchical porous micron column structure was constructed by a hydrothermal method using H6]·6H2O as a precursor, cobalt nitrate as an auxiliary cobalt source, and iron foam as a conductive substrate. 11 / NiCoFe-LDH@IF is an alkaline water electrolysis catalyst with both stability and catalytic activity. NiCoFe-LDH is a layered NiCoFe trimetallic hydroxide. LDH is the abbreviation of Layered Double Hydroxides. Mo4O 11 / NiCoFe-LDH@IF under alkaline conditions 10 mA cm -2 The overpotentials of hydrogen evolution reaction are 48mV and the overpotentials of electrocatalytic oxygen evolution are 250mV, which further enhances the catalytic performance and is superior to Pt and its derivative catalysts.
4. The method according to claim 2 is used in alkaline conditions and 10 mA cm -2 Under a current density of , the synthesized MoNiCoFe multi-metal self-supporting electrocatalyst continuously works for 48 hours without voltage decay of hydrogen evolution reaction, and continuously works for 24 hours without voltage decay of oxygen evolution reaction, thereby concluding that the MoNiCoFe multi-metal self-supporting electrocatalyst of the present invention is a stable catalyst for electrocatalytic water decomposition to produce hydrogen.